A READING OF PSYCHOSIS IN CONTEMPORARY TIMES (REMUNOM, 2025)
This paper examines the configurations of psychosis in contemporary times, focusing on thedifferences between classical psychosis and ordinary psychosis. The aim is to connect theseconceptualizations with the transformations of the contemporary master's discourse, in orderto understand their effects on the subjectivity of the time. The work revisits Freud'sformulations, which conceived of psychosis as the result of the self's radical rejection ofincompatible representations, leading to a rupture with reality and the creation of a newinternal reality marked by hallucinations and delusions. Lacan, in revisiting the Freudianconcept of Verwerfung, reformulates it as foreclosure, understanding psychosis based on theabsence of the Name-of-the-Father signifier in subjective structuring, a signifier thatintroduces the function of paternal interdiction.Based on these foundations, the concept of ordinary psychosis is considered as a way tounderstand contemporary clinical manifestations in their diagnostic subtlety, given thepluralization of Names-of-the-Father and psychiatric diagnoses. At the same time, it isimportant to emphasize that the modes of relationship between the subject and the socialOther, the constitution of the symptom, and its connection with unconscious knowledge areintimately linked to the scientific development of each era. Thus, if in the past, hystericalparalysis was related to advances in neurology, in contemporary times, depression, anorexia,drug addiction, and ordinary psychoses emerge as symptomatic responses to socialtransformations. These manifestations can be understood as a result of the decline of idealssustained by the Other, the imperative of consumption, and the strengthening ofneuroscientific discourse, which guides pharmaceutical production. Thus, it is evident thatcultural and scientific changes directly impact the configuration of contemporarysubjectivity.